Access to clinical trials for adolescents with soft tissue sarcomas: Enrollment in European pediatric Soft tissue sarcoma Study Group (EpSSG) protocols. Issue 6 (24th November 2016) - Ferrari, Andrea; Trama, Annalisa; De Paoli, Angela; Bergeron, Christophe; Merks, Johannes H. M.; Jenney, Meriel; Orbach, Daniel; Chisholm, Julia C.; Gallego, Soledad; Glosli, Heidi; De Salvo, Gian Luca; Botta, Laura; et al.
Abstract: Background: Adolescents with cancer are enrolled in clinical trials at far lower rates than children. This report compares the number of adolescents (15–19‐year‐olds) and children (0–14‐year‐olds) enrolled in the protocols of the European pediatric Soft tissue sarcoma Study Group (EpSSG) with the number of cases expected to occur. Methods: The observed‐to‐expected (O/E) ratio was detected in the EpSSG countries contributing most of the cases, that is, Italy, France, Spain, the Netherlands, United Kingdom, and Ireland. The observed cases included patients enrolled in any of the EpSSG protocols from October 2008 to October 2015, when all EpSSG protocols were open in these countries. The number of expected cases was calculated from the incidence rates estimated throughout the RARECAREnet database in the countries' population‐based cancer registries. Results: In the countries considered, 2, 118 cases aged 0–19 years were enrolled in the EpSSG trials from 2008 to 2015: 82.8% were children and 17.2% were adolescents. The O/E ratio was 0.30 among patients 15–19 years old, as opposed to 0.64 for those 0–14 years old. The O/E ratio differed for the different subtypes: in adolescents, it was 0.64 and 0.18 for rhabdomyosarcoma (RMS) and non‐rhabdomyosarcoma soft tissue sarcomas (NRSTS), respectively; in children, it was 0.77 and 0.50, respectively. The O/E ratios differed across the countries considered. Conclusions: Adolescents were less well represented than children on the EpSSG protocols, with better enrolment for RMS than for NRSTS for all age groups.